(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2019)
Nursing, as an integral part of the health care system, has its unique distinction among other disciplines. Nursing scope of practice has undergone tremendous changes over the past 50 years. Many changes in the health care industry include a setting for health care shifting from hospital and institution-based settings to community-based care. This study determined the proficiency level of the Department of Health’s deployed nurses in client care and leadership and management. Using the descriptive-evaluative research design. Frequency counts and the percentage were employed to identify the characteristics of the respondents and weighted mean to establish their proficiency level on client care and leadership and management along with their areas of responsibility. The Pearson Product Moment Correlation Test or Pearson R was used to determining whether or not there is a significant relationship between the profile and proficiency level of the respondents. Results show that the deployed nurses were very highly proficient in client care as well as in leadership and management. Also, it was revealed that there is no significant relationship between the profile of the respondents and their proficiency in the areas of responsibility in client care and leadership and management; however, there could be other factors affecting their proficiency. Thus, a development program was formulated to further develop and sustain the proficiencies of nurses which were already excellent. The development program is recommended for validation and verification and its adoption upon the establishment of its feasibility.